Spatiotemporal patterns of culvert use by terrestrial Mediterranean mammals - Mouta, Catarina Feliciano (2021)
Culvert flooding jeopardizes their use as safe crossing locations for animals, especially in locations with significative precipitation. The installation of elevated dry ledges inside culverts has been studied as a solution, although it is still not certain how effective they are. In order to tackle this problem, we tried to understand the under-road crossing patterns of mammals in culverts with and without ledges. We got enough data for six species, which showed carnivores had distinct preferences regarding culvert design and that culvert use was also dependent on environmental features surrounding it. Structure openness, distance to the nearest passage, water inside the culvert and season were the variables that most influenced crossing probabilities. Responses to these variables varied among species, highlighting the need for different type of structures that can fulfil each species’ necessities; RESUMO: “Padrões espaciotemporais de uso de passagens hidráulicas por mamíferos mediterrânicos terrestres” A inundação das passagens hidráulicas põe em risco o seu uso como locais de atravessamento seguro para os animais, especialmente em locais onde a precipitação é significativa. A instalação de passadiços elevados tem sido usada como solução, no entanto ainda não é conhecida com rigor a sua eficiência. Para tentar resolver este problema, estudámos os padrões de atravessamento por mamíferos em passagens com e sem passadiços. Apesar de só terem sido reunidos dados suficientes para seis espécies, determinámos que estes carnívoros têm preferências distintas quanto à estrutura da passagem e que o ambiente circundante também é um factor relevante no seu uso. A abertura das passagens, a distância entre elas, a quantidade de água e a estação foram as variáveis que mais influenciaram o uso. As respostas variaram entre espécies, mostrando a urgência de estruturas polivalentes que colmatem as necessidades de cada uma.